Pastoral Konseling bagi Penyintas Christophobia akibat perpindahan Agama dalam Gereja International Full Gospel Fellowship di Manado - Yuwono, Stefanus Christianto; Selanno, Semuel; Mawikere, Marde Stenly (PT. Giat Konseling Nusantara, 2024)
The phenomenon of religious conversion in Indonesia from non-Christians to Christians often triggers Christophobia, which is a form of intolerance and hatred towards Christians which is manifested through discrimination, harassment and violence. The church must be a safe place for survivors of Christophobia and provide a way out as a form of social service to congregation members. Researchers used case study-based qualitative research with a Client-Centered Therapy approach model through interview techniques with seven congregations in the IFGF (International Full-Gospel Fellowship) church in Manado. Pastoral counseling services are a crucial step to care for the holistic well-being of survivors by developing effective strategies to achieve their recovery goals. Recovery does not occur instantly but rather through a gradual process that is layer by layer and religious conversion is a complex matter so counselors must be sensitive.